Smart partnership between Universiti Teknologi Malaysia and FELDA Johor Bahru: Increasing interest in English and parents’ commitment - Muhammad, Faruk; Abdul Majid, Norazman; Puteh, Fatimah; Bunari, Ghazali (2004)
Smart partnerships formed between universities and communities have successfully solved many problems and enhanced the strengths of both parties. This case study examines the structures, resources, and processes that have formed and sustained one successful university-industry partnership in Malaysia. This study is based on a project “inculcating interest in English among children of Tenggaruh community area”, which aims to increase interest among students in rural areas to like, learn and use English. This paper focuses on 1) the benefits - building interest in the English language and commitment from parents in the rural area; and 2) the activities carried out in the project. The nine principles of good practice for community-campus partnership informed the study. A qualitative data-collection of background, interviews and observations are used to identify the personal experience of individuals involved (i.e administrators, facilitators, parents, community leaders and literacy teachers). The results show evidence that the four-year collaboration met all the nine principles of community-campus partnership, in terms of sharing of leadership and resources, people, guidelines and course of action to support the goals of the partnership. Students showed increased interest in the language; and the parents are committed to the sustenance of English use at home.